Plan de marketing digital y su impacto en los atractivos turísticos del cantón Pichincha, año 2022 - Bravo de la Cruz, Sandra Janeht (2022)
The theme "DIGITAL MARKETING PLAN AND ITS IMPACT ON THE TOURIST ATTRACTIONS OF THE PICHINCHA CANTON, YEAR 2022" has been chosen, since there was a problem with this type of site in terms of the services it offers, and how difficult it takes them reach the purposes that are raised in terms of income and the number of visitors that generally occur in the year. For this reason, it is described to measure the impact caused by this plan in said tourist attractions. Information was collected where, according to the leaders magazine, there are around 100 enterprises in the Pichincha Canton, of which 12 belong to tourist attractions in the area. The methodology used was observational and descriptive research because the behavior and decisions of the respondents were studied. The collection of information through the questionnaire tool executed the survey technique to its owners where it was detected that half know the planning through a Digital Marketing system that they even execute in their businesses, while we also came to the conclusion that; It is necessary to train these entrepreneurs so that they know a little more about digital marketing. As a proposed model, the link between the Municipal Government and these entrepreneurs is analyzed so that they are trained on the subject, so that they can eventually put it into practice to improve their services.